Penerapan Media Wordwall pada Pembelajaran Bahasa Indonesia untuk Meningkatkan Literasi Siswa Kelas 2 SD - Hartati, Ulifah Rachmi; Nuvitalia, Duwi; Rina Sugianti, Kristiani (STKIP Andi Matappa Pangkep, 2024)
The aim of the research is to determine students' literacy abilities after implementing Wordwall learning media. Wordwall is a technology-based learning media that can help students understand subject matter in a more fun and interactive way. The research analysis method used is a qualitative method with a descriptive approach. The implications of this research emphasize the importance of using interactive media in improving Indonesian language learning outcomes for grade 2 elementary school students. This study evaluates the effectiveness of implementing Word Wall media in learning Indonesian for grade 2 elementary school students. Through a descriptive analysis approach, this research observes increases in student literacy skills, motivation and learning outcomes. The research results show that the application of Wordwall media makes a significant positive contribution to students' literacy skills compared to conventional methods.